P-013 Use of the Solitaire Device for Emergency Revascularization of the Superior Mesenteric Artery. (29th July 2016) - Dalfino, J; Paul, A; Hnath, J
Abstract : Background: The Solitaire device (Medtronic) was designed for thrombectomy in acute stroke, but its 4–6 mm diameter makes it potentially well suited for peripheral embolectomy cases. In this report, we demonstrate the use of a 6 × 30 mm Solitaire device to revascularize the superior mesenteric artery in a patient with acute mesenteric ischemia. Methods: A 62 year old woman with a history of endometrial cancer and radiation enteritis presented to the emergency department with two days of nausea, vomiting, and increasing abdominal pain. A CT scan of the abdomen with contrast revealed thrombosis of the proximal superior mesenteric artery (SMA) not seen on an abdominal CT performed two months previously (not shown). The patient was placed on a heparin drip and seen emergently by a vascular surgeon who performed a selective SMA angiogram confirming that the main trunk of the SMA was occluded (Figure 1A ). Recanalization of the SMA was attempted with both balloon angioplasty and intra-arterial tPA. Salvage treatment using the Solitaire device was then attempted as a joint procedure between vascular surgery and neurosurgery. A 7 F Cook Shuttle sheath (Cook Medical) was placed into the SMA. A Prowler Select Plus microcatheter (Codman) was then advanced through the clot and into a distal SMA branch over a 0.014" Synchro-2 Soft (Stryker Neurovascular) wire. After performing a microcatheter run to make sure that the distal end of the microcatheter was beyond the clot, a 6 mm x 30 mm Solitaire clot retrieval device (Medtronic) was deployed across the lesion. The Solitaire device was left in place for 5 minutes and then pulled back into the Cook Shuttle sheath. Continuous suction was applied to the sheath during clot retrieval using a 60 cc syringe. A post-thrombectomy angiogram showed full recanalization of the proximal SMA and right main trunk and partial recanalization of the left trunk (Figure 1B ). Results: The patient tolerated the procedure well. Her abdominal pain decreased over the next 48 hours and she was able to resume a normal diet. She was started on Coumadin, but later transitioned to aspirin due to difficulties in maintaining a consistent INR. Conclusions: The techniques and equipment used for acute stroke intervention may be suitable for acute recanalization of peripheral vessels, under the right circumstances. As with many surgical interventions, a multidisciplinary approach may at times yield a novel and effective strategy for a difficult clinical problem. Disclosures: J. Dalfino: None. A. Paul: None. J. Hnath: None.